Greek Logistics : Unlocking Growth Potential through Regulatory Reform and Complementary Measures - World Bank (Washington, DC, 2014)
The World Bank Group (WBG) wrote this report as part of a project designed to assess the competitiveness of the logistics sector in Greece and to develop policy recommendations. The World Bank is carrying out the project at the request of the Greek Ministry of Development, Competitiveness, Infrastructure, Transport, and Networks (currently split into the Ministry of Development and Competitiveness and the Ministry of Infrastructure, Transport and Networks). The report is part of a technical assistance package provided by the World Bank Group to the Government of Greece on enhancing the business environment and trade logistics. The package has been facilitated by the Task Force for Greece (TFGR, an arm of the European Commission), which arranged the financing from the EC technical assistance budget. The document is structured in the following way: First, it provides an overview of the state of logistics in Greece, comparing the country to its peers and highlighting some of the important features that distinguish the country's situation. Second, it provides detailed, technical observations on specific aspects of the logistics environment in Greece. Third, the report describes key actions, drawn from both expert observations and the working groups' conclusions that the Greek government may want to undertake to improve its logistics performance. Finally, in the Annexes it describes the intensive, consultation process that is allowing key stakeholders within the business and policy-making communities in Greece to provide inputs for a national logistics strategy.